Isolation and molecular characterization of Dichelobacter nodosus isolated from sheep in Brazil - Carvalho, Vitor Santiago de; Scherer, Charles Fernando Capinos; Lents, Maicon Pereira; Guimarães, José Eugênio; Almeida e Macêdo, Juliana Targino Silva; Nascimento, Karla Alvarenga; Pedroso, Pedro Miguel Ocampos (Acta Scientiae Veterinariae, 2018)
Background: Pododermatitis or footrot is an infectious disease that affects the hoof and interdigital tissue of sheep causing lameness. The disease is caused by the interaction of the agent Dichelobacter nodosus and symbiotic bacteria in the complex environment of the epidermal tissues of the hoof and host immune system. D. nodosus is not able to invade healthy hooves, so the infection is preceded by colonization of the interdigital skin by Fuso bacterium necrophorum. The aim of this research was to perform the isolation andcharacterization of D. nodosus in sheep farms of different municipalities of Bahia, obtaining the serogroups present in each herd. Materials, Methods & Results: The study was carried out in nine sheep farms from eight municipalities in the state of Bahia. All farms presented history of foot diseases. A total of 620 animals were observed, 140 of which were examined for lameness. To collect the contents of the lesions, sterile swabs were introduced into tubes containing sterile Thorley transport medium under refrigeration at 8°C and sent for laboratory analysis. Subsequently, each swab collected was seeded in two Petri dishes containing 4% hoof agar medium and incubated in anaerobic at 37°C for 96 hours. The purified samples were seeded on 2% hoof agar and incubated under the same conditions as above. The colonies were identified by the morphological characteristic and Gram staining. The DNA was extracted and stored at -20°C until its use in PCR, for identification and classification of D. nodosus in serogroups (A-I). In the nine farms visited were found animals with clinical signs of infectious pododermatitis. After processing, there was success of isolation in 39 samples (41%), confirming the presence of D. nodosus in all municipalities evaluated. Seven serogroups (A, B, D, E, F, H, I) were identified, totalizing 52 positive cases involving these serogroups, being the most prevalent the serogroups D, with 59% of the cases (31/52) and H with 17% (7/52). Of the total samples, 11.5% had mixed infections with more than one serogroup per animal. Infection by up to two serogroups was found in 9.5% of the samples. Infection by more than two serogroups was found in only 2.1% of the samples of the present study. Discussion: The variations found in the number of affected animals and evolution of the lesions can be explained by the nature of the strains present in each farm and by epidemiological factors. According to the literature, it is possible to observe percentage variations of success in culturing D. nodosus either in different countries or in different regions within the same country, finding larger, smaller and similar values to this work (41%). These variations usually occur for reasons related to the quantity and viability of the bacteria in the samples. Thus, the number of bacteria in the lesion, degree of contamination with other bacteria, type and use of means of transport, besides the time elapsed among the collection, packaging and shipment are primordial elements to reach good isolation rates. Among all the serogroups found in this experiment, D and H were the predominant ones. The present work is the first in Brazil to characterize isolates of D. nodosus by PCR, a more accurate molecular technique than the previously used technique, based on microagglutination, and the first report in the country involving serogroup I, including mixed infections of this species (D + H + I) and other serogroups (E + F, D + H). Thus, the knowledge of the serogroups prevalent in a given state or country is directly related to both prevention and eradication of the disease.